A history of India - Kulke, Hermann; Rothermund, Dietmar (Routledge, Taylor & Francis Group, 2016)
ch. 1. Early civilisations of the Northwest -- chapter 2. The great ancient empires -- chapter 3. The regional kingdoms of early medieval India -- chapter 4. Religious communities and military feudalism in the late Middle Ages -- chapter 5. The rise and fall of the Mughal Empire -- chapter 6. The period of colonial rule -- chapter 7. The freedom movement and the partition of India -- chapter 8. The Republic.
Keywords: India -- History